Gene expression analysis of slected ribosomal protein genes in Nasopharyngeal cells - Ng, Kiaw Kiaw (Universiti Malaysia Sarawak, UNIMAS, 2008)
Ribosomal proteins (RPs) are the essential constituents of ribosomes in all organisms. The investigations, to date, have reported the implication of ribosomal proteins in tumourigenesis. Recently, a preliminary study revealed the down-regulation of RPS26 and RPS27 genes in nasopharyngeal carcinoma (NPC) relative to normal nasopharyngeal tissues. Hence, it is essential to study the gene expression of both RPS26 and RPS27 in NPC in order to obtain an insight into the actual roles and precise mechanism of these two ribosomal proteins in tumourigenesis of NPC. This project aimed to evaluate the gene expression patterns of both RPS26 and RPS27 in NPC at transcript and protein level using comparative reverse-transcription polymerase chain reaction (RT-PCR) and Western analysis. In this study, total RNA isolated from normal nasopharyngeal mucosa tissues, NPC tissues and NPC cell lines were successfully amplified with RT-PCR. Specific bands of PCR products with estimated size of 572 bp and 300 bp were obtained for RPS26 and RPS27 genes respectively. RPS26 mRNAs was found to be up-regulated in NPC cell lines and tissues relative to normal nasopharyngeal mucosa. However, there is no significant difference for RPS26 and RPS27 mRNA expression in both NPC tissues and NPC cell lines relative to the normal nasopharyngeal mucosa. Moreover, no significant variation was observed for RPS26 and RPS27 mRNA expression among three different cell lines.